Estetika Karya Seni Lukis Faiz Zaki Abdillah: Perspektif Teori Monroe C. Beardsley - Aditya Eko Adrianto; I Nyoman Suyasa; Syamsiar; Thoriq Bidar Dardiri (Institut Seni Indoensia Surakarta, 2025)
This study analyzes the paintings of Faiz Zaki Abdillah using a descriptive qualitative approach, with Monroe C. Beardsley's aesthetic theory as its primary foundation. The method employed is analytical description, integrating visual analysis and interpretation of three primary works: Life (2022), Morp Transition (2023), and Amartha (2025). The findings indicate that the creative process behind Faiz Zaki Abdillah's paintings encompasses idea conception, concept development, technique and style, and the stages of creation. An aesthetic analysis based on the principles of unity, complexity, and intensity reveals that Faiz's works represent a synthesis of empirical experience and ecological spirituality, shaped by his closeness to nature, animals, and the agricultural world. Through detailed, meticulous, and symbolic visual structures, the ecological spiritual values in his works are organically realized, creating a contemplative and transcendental aesthetic experience. An examination of the creative background further reveals that the aesthetics of Faiz's works are a comprehensive crystallization of his creative process, where form and meaning, technique and spirituality, merge into a coherent, reflective, and aesthetically rich visual narrative.